Stress calculation and failure prevention for microelectronics devices - Wang, Fengtao (2012)
This project presents a numerical investigation on the thermo-mechanical reliability of microelectronics devices. Thermo-mechanical reliability is one of the major bottlenecks for both current and future microelectronics devices. The current finial year project is to study the Stress Calculation and Failure Prevention for Microelectronics Devices. Three major cases are investigated: 1) Hygro-thermal Induced Crack in Microelectronic Devices; 2) CTE Mismatch Induced Cracking in Microelectronic Devices; 3) Crack Tip Plastic Zone and Crack Tip Opening Displacement. Simulation work using the commercial Finite Element software ABAQUS are conducted to analyze the practical thermal problems with various parameters considered. It is found that materials used in the manufacturing process could greatly affect the reliability of microelectronics devices.